Análise conceitual do termo socioemocional em psicologia e percepção de professores de escola pública sobre a relação professor-aluno e com o contexto de trabalho - Cardoso, Ariela Santana (2017)
The research on "social-emotional" terminology has been used in Psychology in a dispersed way, in plural contexts and with different ways of defining it. The theme of socioemotionality and receiving investments for research around education. Still, with a greater concentration of studies with children and young people, in addition to the prevalence of quantitative research. In this context, a population of teachers has been little investigated in relation to their perceptions of relations with students and school. These perceptions are relevant in that they raise teachers' demands on how advanced educational actions for students and improve feelings of job satisfaction. Two studies compose the present dissertation, being a conceptual analysis and an empirical study. The conceptual analysis explores empirical studies of the last ten years around Psychology that use the term socioemotional. The objective of the research was evaluated as the concept has been employed, defined, in its contexts, its operationalization and as measures used in the different researches. The search returned 74 articles, being only two national articles. There has been an increase in the number of studies using the term over the past five years, with the prevalence of studies around education and development. In all, 26 terms related to the socioemotional term were found, so that the term "socioemotional" adjective used terms in the studies. In all, 73% of the studies did not operationalize the concept of social-emotional, although 66% of the studies propose to measure socioemotionality dimensions. In view of the results obtained in the first study, we chose to develop a qualitative study in teachers, since they are presented in a less expressive way. The empirical study aimed to investigate a perception of teachers about their relationship with students and a school in a sample of public elementary school teachers in Porto Alegre. In all, 16 teachers participated in focus group discussions about perceptions of their relationship with their students and their relationship with the school. Teachers were divided into two groups, with a first phase and another with the second phase of elementary education. The researcher asked guiding questions about teacher-student relationships and their relationship with a school. How teachers' statements were recorded and later transcribed and analyzed. A thematic analysis was conducted, in which the categories emerged from the speeches of the participants. The results pointed to a need for dialogue between teachers, school, community, and government for greater effectiveness of education actions. In addition, a promotion of information about a value as educational actions for a community to improve their relationships.